Towards an ethics for telehealth - Botrugno, Carlo (Nursing ethics, 2019)
Over the last two decades, a public rationale for the implementation of telehealth has emerged at the interplay of specialised literature and political orientations. Despite the lack of consistent findings on the magnitude of its benefits, telehealth is nowadays presented as a worthy solution both for patients and healthcare institutions. Far from denying the potential advantages of telehealth, the main objective of this work is to provide a critical assessment on the spread of the remote services as a vector of positive transformation of contemporary health systems. For pursuing this objective, the EU agenda for the promotion of telehealth will be retraced, and the main evidences alleged to sustain the implementation of remote care services will be assessed. Furthermore, it will be evaluated the attempt made by the European Commission to establish an ethical framework for guiding the use of telehealth in daily practice, and a roadmap of the most relevant legal and ethical issues posed by the spread of telehealth will be traced. In the conclusions, it will be argued that the radical transformations induced by this form of technological innovation call on to a new, ad hoc ethics through which critically evaluate benefits and implications of telehealth services, with a view to keep high the standard of healthcare against the economic interests of private stakeholders and ICTs’ vendors.